Lower circulating levels of chemokine CXCL10 in Helicobacter pylori-infected patients with peptic ulcer: Influence of the bacterial virulence factor CagA - Jafarzadeh, Abdollah (Tehran University of Medical Sciences, 2013)
BACKGROUND AND OBJECTIVES: Alterations in CXCL10 (a Th1 chemokine) expression have been associated with various diseases. The aim of this study was to evaluate the serum CXCL10 levels in H. pylori-infected patients with peptic ulcer (PU), H. pylori-infected asymptomatic (AS) subjects and healthy H. pylori-negative subjects, and also to determine its association with bacterial virulence factor cytotoxin-associated gene A (CagA). MATERIALS AND METHODS: Serum samples from 90 H. pylori infected patients with PU (70 were anti-CagA (+), 20 were anti-CagA (-)), 65 AS carriers (40 were anti-CagA (+), 25 were anti-CagA (-)) and 30 healthy H. pylori-negative subjects (as a control group) were tested for concentrations of CXCL10 by using the ELISA method. RESULTS: The mean serum levels of CXCL10 in PU patients (96.64 ± 20.85 pg/mL) were significantly lower than those observed in AS subjects (162.16 ± 53.31 pg/mL, P < 0.01) and the control group (193.93 ± 42.14 pg/mL, P < 0.02). In the PU group, the serum levels of CXCL10 in anti-CagA (+) subjects was significantly higher in comparison to anti-CagA (-) patients (P < 0.04). CONCLUSION: These results showed that the mean concentrations of CXCL10 in H. pylori-infected-PU patients was lower than AS carriers and control group. In the PU group, the serum levels of CXCL10 were associated with bacterial factor CagA.